2022
DOI: 10.3390/ijms232113191
|View full text |Cite
|
Sign up to set email alerts
|

Opaganib Protects against Radiation Toxicity: Implications for Homeland Security and Antitumor Radiotherapy

Abstract: Exposure to ionizing radiation (IR) is a lingering threat from accidental or terroristic nuclear events, but is also widely used in cancer therapy. In both cases, host inflammatory responses to IR damage normal tissue causing morbidity and possibly mortality to the victim/patient. Opaganib, a first-in-class inhibitor of sphingolipid metabolism, has broad anti-inflammatory and anticancer activity. Opaganib elevates ceramide and reduces sphingosine 1-phosphate (S1P) in cells, conditions that increase the antitum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Efficacy of early treatment with opaganib. We previously reported that ad tion of opaganib to mice exposed to high-dose TBI with 5% bone marrow shiel tected the animals against GI-ARS and markedly improved 30-day survival [34] experiments, opaganib treatment was not started until 24 h after radiation exp model use of the drug as a medical countermeasure (MCM) to mitigate GI-ARS intentional, e.g., accidental or terroristic, radiation exposure. We therefore con similar short-term, post-radiation exposure experiment to determine if the opaga ment regimen that was active against GI-ARS improved the longer-term surviva Therefore, male C57BL/6 mice were exposed to 16 Gy TBI with 5% bone marrow and then treated with 0 or 150 mg/kg opaganib twice-daily (BID) for 5 days, beg h after irradiation (Groups B and C, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Efficacy of early treatment with opaganib. We previously reported that ad tion of opaganib to mice exposed to high-dose TBI with 5% bone marrow shiel tected the animals against GI-ARS and markedly improved 30-day survival [34] experiments, opaganib treatment was not started until 24 h after radiation exp model use of the drug as a medical countermeasure (MCM) to mitigate GI-ARS intentional, e.g., accidental or terroristic, radiation exposure. We therefore con similar short-term, post-radiation exposure experiment to determine if the opaga ment regimen that was active against GI-ARS improved the longer-term surviva Therefore, male C57BL/6 mice were exposed to 16 Gy TBI with 5% bone marrow and then treated with 0 or 150 mg/kg opaganib twice-daily (BID) for 5 days, beg h after irradiation (Groups B and C, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Efficacy of early treatment with opaganib. We previously reported that administration of opaganib to mice exposed to high-dose TBI with 5% bone marrow shielding protected the animals against GI-ARS and markedly improved 30-day survival [34]. In those experiments, opaganib treatment was not started until 24 h after radiation exposure to model use of the drug as a medical countermeasure (MCM) to mitigate GI-ARS from unintentional, e.g., accidental or terroristic, radiation exposure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, Bonnaud et al [ 231 ] demonstrated that S1P protected human microvascular endothelial cells from ceramide-induced apoptosis following 15 Gy of IR, but not from DNA damage-induced mitotic death. Most notably, opaganib, a first-in-class inhibitor of sphingolipid metabolism via SPHK2, has been shown to deliver broad anti-inflammatory (via the downregulation of NF-κB and TNFα) and anti-cancer activity [ 232 ]. As such, opaganib acts as a sphingosine mimetic molecule and also inhibits DES1, thereby increasing levels of dihydroceramides and promoting autophagy [ 233 ].…”
Section: Sphingolipids In Bone Homeostasis and Diseasementioning
confidence: 99%